KARAKTERISASI PENGARUH PENGHALANG BOLA BESI TERHADAP MEDAN MAGNET, UNTUK PEMANFAATAN ALAT UKUR VISKOSITAS FLUIDA METODE BOLA JATUH MENGGUNAKAN SENSOR HALL EFFECT UGN 3503 - Firdaus, M (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2023)
The characterization of the UGN 3503 hall effect sensor on the influence of the iron ball barrier from the magnetic field aims to improve the design of a tool for measuring fluid viscosity using the falling ball method. The UGN 3503 hall effect sensor used is a magnetic field sensor, research needs to be carried out to find the characteristics of this sensor regarding the distribution of the magnetic field under the influence of iron ball barriers so that it can be used for designing fluid viscosity measuring instruments. Characterization was carried out by bringing the UGN 3503 hall effect sensor closer to a Niodinium permanent bar magnet source, and positioning an iron ball between the two with variations in the volume of the iron ball and variations in distance vertically and horizontally from the sensor side. This research is intended to determine the size of the sensor output and the strength of the magnetic field with respect to variations in distance and volume of the iron ball. Data collection was carried out 3 times. The results of research on variations in the volume and distance of the ball horizontally or parallel between the sensor and the magnet show that at a distance of 30 mm between the sensor and the magnet, variations in the distance of the iron ball are closer to the sensor and the volume of the iron ball is larger, in this case the size of the iron ball is used with a diameter of 14 mm, an average magnetic field strength output of 92 Gs to 124,667 Gs is obtained, so it is good to use for designing a fluid viscosity measuring instrument using the falling ball method. Meanwhile, variations in the volume and distance of the ball vertically or perpendicular to the parallel axis between the sensor and the magnet, with a distance of 20 mm from the magnet, show a magnetic field strength output of 78.3 Gs to 133.33 Gs in the 14 mm diameter iron ball experiment, with a peak field strength at a vertical distance of the iron ball between 8-13 mm or 5 mm below the parallel axis between the sensor and the magnet. The sensor can detect the presence of a magnetic field better when the magnetic field source is in the right direction with the sensor and if it is in a wide magnetic field. The different positions of the iron balls and their sizes affect the measurement results of the sensor output and the strength of the magnetic field.